From peasant guerrillas to urban civilians: the peace process in Colombia peace process in Colombia 2016-2024 - Sierra-Moreno, Olmo-Jesús (2025)
Introduction: the implementation of the peace agreement in Colombia has posed significant challenges for its signatories, who have had to adapt to a reality far removed from their previous experiences—whether in rural life or in hiding. Objective: this study examines the transformations in the daily lives of the peace agreement’s signatories following its implementation. Methodology: between 2017 and 2024, interviews were conducted with 15 signatories of the agreement, focusing on their everyday experiences and the challenges encountered during the reincorporation process. The analysis revealed three major obstacles affecting their daily lives: unemployment, security concerns, and inadequate housing access. These challenges have significantly diminished their quality of life, hindered full societal integration, and undermined the anticipated success of the reincorporation process. Conclusions: the current reincorporation model, which remains overly focused on demobilization, must be re-evaluated. A more comprehensive approach is needed to ensure the signatories’ effective integration as citizens and the long-term sustainability of peace in Colombia.